Behavioral and Organizational Drivers of SAK EMKM Adoption In MSMEs - Fitrarena Widhi Rizkyana; Niswah Baroroh; Nitis Welasih (SENTRALISASI, 2026)
The Execution of Financial Accounting Standards (SAK EMKM) is important for the credibility and reliability of financial statements. However, only about 1.49% of MSME actors in Pemalang are receiving guidance from the local government. It indicates the need to examine determinants influencing its implementation. The focus of the current investigation is the interaction of accounting understanding, perceived usefulness, and the socialization of SAK EMKM, with business readiness as a moderator. Primary data were collected, and 114 MSME owners/managers in Pemalang Regency were selected through purposive and snowball sampling. Partial Least Squares Structural Equation Modeling (PLS SEM) was used to analyze the data, and SmartPLS 3.0 was used to conduct model testing. The developed model explained 71% of the variance in SAK implementation. The main findings of the study were that understanding accounting, perceived usefulness, and the socialization of SAK EMKM positively contributed to its implementation. However, business readiness has not moderated the relationship between accounting knowledge, perceived usefulness, and the socialization of SAK EMKM during its implementation. The research findings indicate that behavioral and perceptual factors are more important than structural factors in explaining MSMEs' adoption of the SAK EMKM. Implementation of this standard is driven more by the level of understanding and perceived usefulness than by formal business readiness. In practice, these research findings empower regulators and the government to strengthen structured outreach and technical assistance to enhance the broader potential for implementation of the SAK EMKM.